A glucose biosensor using methyl viologen redox mediator on carbon film electrodes - Ghica, Mariana Emilia (2005)
A new methyl viologen-mediated amperometric enzyme electrode sensitive to glucose has been developed using carbon film electrode substrates. Carbon film electrodes from resistors fabricated by pyrolytic deposition of carbon were modified by immobilization of glucose oxidase through cross-linking with glutaraldehyde in the presence of bovine serum albumin. The mediator, methyl viologen, was directly immobilised with the enzyme together with Nafion cation-exchange polymer. The electrochemistry of the glucose oxidase/methyl viologen modified electrode was investigated by cyclic voltammetry and by electrochemical impedance spectroscopy. The biosensor response to glucose was evaluated amperometrically; the detection limit was 20 [mu]M, the linear range extended to 1.2 mM and the reproducibility of around 3%. When stored in phosphate buffer at 4 °C and used every day, the sensor showed good stability over more several weeks.